49th Don Carlos Palanca memorial awards for literature - Coscolluela, Elsa (Animo Repository, 1999)
Elsa Coscolluela, a DLSU alumna, won first place in the full length play in English during the 49th Don Carlos Palanca Memorial Awards for Literature. Her work was titled Original Grace.